Subjective dimension in the analysis of human development - LÓPEZ NOVAL, Borja; DOMÍNGUEZ MARTÍN, Rafael (Revista Iberoamericana de Estudios de Desarrollo)
In recent years subjective evaluations about own quality of life, resumed in levels of life satisfactionor happiness, are gaining importance as indicators of development. Some authors state that subjectivewell-being is a necessary and sufficient condition for human development. In this work the arguments ofthese authors are explained and it is discussed the role subjective evaluations must play on developmentstudies. The main conclusion is that although it is necessary to integrate subjective well-being into humandevelopment studies we cannot identify subjective well-being and development.